FACTORS CONTROLLING STERILITY IN CANNED PRAWN - CHAUDTTTTRI, D R; GOPALAKRISHNA IYER, T S; PILLAI, V K (Fishery Technology, 2025)
Probable sources of contamination of raw, blanched andprocessed meat at various stages of handling and methods for theirrectification have been described in the paper. Inter-relationshipbetween absolute sterility and commercial sterility with particularreference to the sanitation of the factory has been discussed.